2007
DOI: 10.1016/j.jvs.2007.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Silent ischemia after neuroprotected percutaneous carotid stenting: A diffusion-weighted MRI study

Abstract: BACKGROUND AND PURPOSE: To assess by diffusion-weighted MR imaging (DWI) the efficacy of cerebral protection devices in avoiding embolization and new ischemic lesions in patients with severe internal carotid artery (ICA) stenosis undergoing carotid artery stent placement (CAS). METHODS: One hundred sixty-two CASs in the extracranial ICA were performed with the use of distal filters. Mean age of the patients was 68.5 years (range, 33-86) and 122 patients (75.3%) were symptomatic. MR imaging was performed in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
75
1
20

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(106 citation statements)
references
References 24 publications
(32 reference statements)
10
75
1
20
Order By: Relevance
“…30) Cerebral embolic events may occur during diagnostic angiography performed at early CAS caused by thromboembolism or air embolism introduced by injection of contrast medium or catheter flushing. 23) The apparently high incidence of contralateral lesions matched previous studies using diagnostic angiography. New ischemic lesions occurred in 29% of 59 patients after diagnostic angiography, and the frequency of lesions was correlated to the amount of contrast medium, timing of the procedure, number of vessels difficult to probe, and use of more than one catheter.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…30) Cerebral embolic events may occur during diagnostic angiography performed at early CAS caused by thromboembolism or air embolism introduced by injection of contrast medium or catheter flushing. 23) The apparently high incidence of contralateral lesions matched previous studies using diagnostic angiography. New ischemic lesions occurred in 29% of 59 patients after diagnostic angiography, and the frequency of lesions was correlated to the amount of contrast medium, timing of the procedure, number of vessels difficult to probe, and use of more than one catheter.…”
Section: Discussionsupporting
confidence: 75%
“…Microembolic lesions detectable with diffusion-weighted imaging appeared in 26% of patients treated with a distal filter device versus 36% of patients treated with unprotected CAS. 8) A series of 162 CAS procedures involved distal ischemic events in 17.3% of patients, and the number of lesions per patient was 2.07, 23) compared to 2.8 in our study. However, all filtration devices have programmed pores to permit antegrade blood flow, which may allow particles smaller than the pore size to pass through the filter, and these Distal Ischemia After CAS small microemboli may not be visible using diffusion-weighted imaging.…”
Section: Discussionmentioning
confidence: 40%
“…However, there is no established relationship between the number of microembolic signals and the incidence of new ischemic brain lesions detected on DWI. 15) Almost all microembolisms produced during CAS are thought to be washed out, as previously proposed. 6) In patients with carotid artery stenosis of more than 50%, a decrease in blood pressure would not produce an active vascular response, but would reduce cerebral blood volume and velocity due to impairment of dynamic cerebral autoregulation.…”
Section: Discussionmentioning
confidence: 82%
“…1.16 % and 0.74 %, respectively, while after carotid stenting CHS and ICH occurred in 1.9 % and 0.37 % of patients correspondingly [4] The study by Saraçoğlu E. et al showed a positive correlation between CHS and oxidative stress biomarkers emphasizing that measurement of oxidative stress perioperatively might play a role in the diagnosis and treatment of the hyperperfusion syndrome.…”
mentioning
confidence: 97%
“…Symptoms such as ipsilateral migraine-like headaches, seizures, and transient focal neurologic defi cits in the absence of cerebral ischaemia in MRI images are attributed to cerebral hyperperfusion syndrome. According to respective literature, incidences of the CHS syndrome after carotid revascularization vary from 0.2 % to 18.9 % [4]. The presence of symptoms is essential to the defi nition of the syndrome.…”
mentioning
confidence: 99%